Migratory Divorce: A Proposed Congressional Remedy - Andrew A. Caffrey (Washington University Law Quarterly, 1952)
It is the thesis of this paper that a review of the procession of cases in which the Supreme Court has unsuccessfully grappled with the problems posed by "inter-state" divorce, dating back to Cheever v. Wilson, decided in 1869, and continuing up to the present decision, make manifest the inadequacy of the judiciary as the agency for resolving these problems. It is this inadequacy of the judiciary's solution which suggests that in definitive legislation may be found a more adequate instrumentality for the elimination of many of the existing uncertainties, conflicts, and difficulties in the administration of divorce laws.
Keywords: Conflict of laws; Divorce and separation